(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Provision of education as a global social service is champion by the public sector. Where these education facilities are located influences their utilization and efficiency. Proximity to these facilities also influences decisions to seek and patronize them. The study analyzes the geo-spatial database and distribution of Government Secondary Schools, using GIS in Chikun Local Government Area. 28 Government Secondary Schools were identified. Their geographic coordinates were established by the use of GPS device and mapped out. The data generated from the field was used to create geo-database of Government Secondary Schools. From the study, 51.4% of registered students were enrolled in the Government Junior Secondary Schools cadre while 58.6% was in Government Senior Secondary Schools. 79% of the student’s enrolments were concentrated in three communities. Nasarawa community was 43.3%, Sabo-Tasha community was 19.4% and Narayi community was 16.5%. These communities form part of Kaduna metropolis with evidence of high population concentration. Queries from the database show only 21.4% of the Schools were with fenced, 7.1% of the schools were with school halls, 25% of the schools were with school libraries and 14.3% of the schools were with computers. The distribution pattern was found to be appearing not different than random using the ArcGIS auto-correlation analysis tool. Government Secondary Schools in the study area appear to be poorly equipped for conducive learning experience. Therefore, the study recommends schools expansion, provision of new schools and upgrading existing schools to standard by all stakeholders.